Mengoptimalkan Implementasi Sistem Keuangan Desa untuk Alokasi Dana Desa yang Efektif di Desa Gunungsari Kecamatan Dawarblandong Kabupaten Mojokerto - Mario Ade Pratama,; Tries Ellia Sandari, (Jurnal Mutiara Ilmu Akuntansi, 2024)
The implementation of the Village Financial System in Gunungsari village has been very effective, this can be seen from the process of preparing the Village Revenue and Expenditure Budget through Siskeudes which is more easily accessible because of the complete features available in the application. As in Permendagri No. 113 of 2014 concerning villages, namely Planning, Implementation, Administration, Reporting, Accountability, reporting process. The type of research used is qualitative research. Data was obtained by conducting direct interviews, observation and documentation in Gunungsari village by obtaining primary data through interviews with resource persons and secondary data obtained from existing documentation in Gunungsari village, village history, general description and financial reports. The research results show that the implementation of the village financial system plays an important role in the efficiency and transparency of the use of village funds. This system requires strict procedures in financial management, including better reporting and accountability.